Kapasitas Adsorpsi Anabaena cycadae Untuk Penyisihan Logam Crom (Cr) Dari Limbah Cair Industri Elektroplating - Juarsa, Tri; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Utilization of algae biomass can be an alternative solution to environmental pollution problems due to heavy metals, because it has an active site and pores on the surface so it can be used in biosorption process. This study was conducted todetermine whether the biosorbent of Anabaena cycadae algae in reducing Cr level of electroplating industry waste water. Biosorbent dose variation are 500 mg /l, 700 mg / l, 900 mg / l and 1100 mg / l, 105Î¼m, 149 Î¼m and 177 Î¼m biosorbent particle size and contact time variations of 30, 45, 60, and 75 minutes wereperformed to determine the effect to the biosorption process. The optimum state was obtained at an algal dose is 900 mg / l, a particle size is 105 Î¼m with a contact time is 60 min. The adsorption capacity of algae in absorbing Cr metal is 2,379 mg / g.Keywords: biosorption, algae biomass, biosorbent mass, pH, contact time, Cr, electroplating wastewater